SISTEM INFORMASI KEPENDUDUKAN UNTUK PENINGKATAN LAYANAN PRIMA KECAMATAN WIDANG JAWA TIMUR - Tining Haryanti; Fierza Fierza (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2024)
The The availability of excellent infrastructure in fulfilling public services is the government's hope in providing services, including in Tuban district, East Java. The lack of technological adaptation in population data archiving has caused slow population registration issues. This dedication aims to produce a functional information system to address population registration problems. With the implementation of the population system in Tuban district, the speed of population services has increased. Consistency in the use of the population system is expected to achieve population data accuracy in real-time conditions.